2010
DOI: 10.1073/pnas.1010262107
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of prethrombin-1

Abstract: Prothrombin is the zymogen precursor of the clotting enzyme thrombin, which is generated by two sequential cleavages at R271 and R320 by the prothrombinase complex. The structure of prothrombin is currently unknown. Prethrombin-1 differs from prothrombin for the absence of 155 residues in the N-terminal domain and is composed of a single polypeptide chain containing fragment 2 (residues 156-271), A chain (residues 272-320), and B chain (residues 321-579). The X-ray crystal structure of prethrombin-1 solved at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 47 publications
4
43
0
Order By: Relevance
“…The occluded conformation of the active site of ProTΔ146-167 is caused mainly by the repositioning of W468 (W148) and not by the collapse of W547 (W215) observed in the structures of other inactive thrombin precursors such as GD-ProT (15), prethrombin-1 (17), and prethrombin-2 (25). The width of the active site of ProTΔ146-167 is similar to that reported for the zymogen of complement factor C1r (26) and trypsinogen (27) and falls toward the lower end of the distribution of trypsin-like zymogens (28) that ranges from 8.1 Å in the zymogen of complement factor D (29) to 14.6 Å in prethrombin-1 (17). Another critical Cα-Cα distance between the catalytic S525 (S195) and D519 (D189) measures the depth of the active site pocket and increases slightly from 14.4 Å in GD-ProT to 15.6 Å in ProTΔ146-167 (Fig.…”
Section: Activationsupporting
confidence: 73%
See 1 more Smart Citation
“…The occluded conformation of the active site of ProTΔ146-167 is caused mainly by the repositioning of W468 (W148) and not by the collapse of W547 (W215) observed in the structures of other inactive thrombin precursors such as GD-ProT (15), prethrombin-1 (17), and prethrombin-2 (25). The width of the active site of ProTΔ146-167 is similar to that reported for the zymogen of complement factor C1r (26) and trypsinogen (27) and falls toward the lower end of the distribution of trypsin-like zymogens (28) that ranges from 8.1 Å in the zymogen of complement factor D (29) to 14.6 Å in prethrombin-1 (17). Another critical Cα-Cα distance between the catalytic S525 (S195) and D519 (D189) measures the depth of the active site pocket and increases slightly from 14.4 Å in GD-ProT to 15.6 Å in ProTΔ146-167 (Fig.…”
Section: Activationsupporting
confidence: 73%
“…Complete disorder was detected in Lnk1, residues 144-168 of Lnk2, and residues 255-273 of Lnk3 containing the site of cleavage at R271. Disorder of Lnk3 was already documented in previous structures of meizothrombin desF1 (16) and prethrombin-1 (17), but the flexibility of Lnk1 and Lnk2 could not be anticipated before the structure of GD-ProT became available. Luminescence resonance energy transfer measurements of prothrombin in solution with probes attached to kringle-1 and kringle-2 have shown that Lnk2 assumes a range of conformations and functions like a flexible spring connecting the kringle-2/protease domain pair on the C-terminal side to the Gla domain/kringle-1 pair on the N-terminal side (15).…”
mentioning
confidence: 92%
“…The crystal structure of the N-terminal portion, composed of the Gla and kringle 1 domains (together known as F1), revealed a tight association between the 2 domains into a single rigid unit. 35 The C-terminal portion of prothrombin is composed of the second kringle domain (K2) and the catalytic domain, which also associate into a rigid unit due to the tight interaction of K2 with the catalytic domain (together known as prethrombin-1 [Pre1] 36 ). F1 and Pre1 are connected by a 26-residue unstructured linker, suggesting that each rigid domain binds independently to prothrombinase.…”
Section: Location Of the Prothrombin Binding Sitementioning
confidence: 99%
“…42 The structural features of Pre1 and meizothrombin, coupled with the identification of the putative substrate binding site on prothrombinase help to rationalize the ratcheting mechanism. The structures of Pre1 and meizothrombin 36,43 show that Pre1 undergoes a large conformational rearrangement when converted to meizothrombin. The conformational change involves the ordering of the catalytic domain and a repositioning of the K2 domain.…”
Section: Substrate Allostery Confers Sequential Processingmentioning
confidence: 99%
“…Although the foregoing provides a reasonable explanation for our findings, it cannot be readily reconciled with all structural information. The F2 domain in the prethrombin 1 structure (lacking the F1 domain) readily superimposes on the F2 domain in the three other structures of prothrombin retaining covalent linkage with K1 and the Gla domain (11,12,31). The pairwise root mean square deviations for these superimpositions ranged from 0.29 -0.78 Å (mean 0.53 Å), suggesting the lack of a major effect of K1 or cleavage at Arg 155 on the folding of K2.…”
Section: Discussionmentioning
confidence: 94%